Conjunction analysis at the tenth Grade Students’ of SMK Telkom 2 Medan - Elia Fransiska; Jonris Tampubolon; Elita Modesta Sembiring (ELT (English Language Teaching Prima Journal), 2022)
The purpose of this study was to describe the students in tenth grade at SMK Telkom 2 Medan's ability to use conjunction. The study's goal is to find out how well the students use conjunction and what obstacles they face. The tenth-grade students at SMK Telkom 2 Medan were the focus of the investigation. The research used qualitative method and analyze data. In collecting the data the researcher used test and interview. From the analysis of data, it was found that there were 4 (13,3%) students were good and categorized able, and 10 (33,3%) students were poor and categorized unable and 16 (53,3%) students were very poor and categorized unable. In this case, students were unable to learn use conjunction. It is concluded that analysis of students’ ability in using conjunction.